The effects of a single bout of exercise on plasma triglycerides, glucose, and insulin following consumption of a high-fat mixed macronutrient meal - Smith, Whitney, author; Melby, Chris, advisor; Hickey, Matt, advisor; Nelson, Tracy, committee member (Colorado State University. Libraries, 2011)
Purpose: The aim of the present study was to examine the effect of a single, acute bout of exercise with caloric replacement compared to a sedentary condition on plasma triglyceride, glucose, and insulin concentrations in response to a high-fat, mixed macronutrient (HFMM) meal challenge. Methods: Eight non-obese, sedentary females aged 19.6 ± 1.3 years participated in two trials: sedentary (SED) and exercise (EX). For the SED trial, subjects refrained from exercise the evening prior to the next morning's HFMM meal. The EX trial was designed to have subjects cycle at 65% of their VO2peak to produce a net energy cost of 400 calories, with a snack provided shortly after to replace the extra calories expended with exercise. However, due to a methodological error, the net energy cost of exercise was less than the targeted value by approximately 100 kcal, which when accompanied by the replacement energy snack, likely resulted in a small acute positive energy balance. Thus, the unintended research question addressed was whether or not a low intensity bout of exercise could attenuate the postprandial lipemic response to a HFMM meal when subjects slightly overcompensated for their exercise energy expenditure. During the trial day subjects reported to the laboratory following a 12-hour overnight fast. Blood samples were obtained by intravenous cannulation before ingestion of the HFMM meal challenge and at 30, 60, 90, 120, 150, 180, 210, 240, 300, and 360 minutes after ingestion. Plasma was analyzed for triglyceride, glucose, and insulin concentrations, with these variables compared across the SED and EX conditions using a repeated measures analysis of variance. Results: There were no significant treatment by time interactions for any of the dependent variables. Low intensity exercise with modest energy overconsumption failed to attenuate the postprandial triglyceride, glucose, and insulin responses to a HFMM meal challenge in comparison to the SED condition. Conclusion: A low intensity exercise bout accompanied by modest energy overconsumption failed to improve the postprandial response to a HFMM meal challenge compared to the HFMM meal challenge without exercise. Exercise alone may not be beneficial in attenuating postprandial lipemia unless it is accompanied by a resulting acute caloric deficit.
Keywords: triglyceride; caloric replacement; glucose; high-fat mixed macronutrient; insulin